Penambahan Core Stability pada Proprioceptive Neuromuscular Facilitation untuk Memperbaiki Kemampuan Ambulasi Pasien Hemiparese Pasca Stroke - Sudaryanto, Sudaryanto; Erawan, Tiar; Nugraha, Rahmat; Hasbiah, Hasbiah; Usman, Nurhayati (FORIKES, 2024)
The degree of disability experienced by stroke patients depends on the severity of the hemiparesis experienced by the patient. Approximately 30-60% of patients with hemiparesis experience changes in ambulation ability. The aim of this study was to determine the effect of adding core stability to proprioceptive neuromuscular facilitation on improving the ambulation ability of post-stroke hemiparesis patients. The design of this research was a randomized pretest-posttest with control group, which involved 2 groups, namely the treatment group that was given core stability and proprioceptive neuromuscular facilitation, and the control group that was given proprioceptive neuromuscular facilitation. Each group consisted of 10 patients, which were determined by random allocation. In both groups,